Identification of the (Pro)renin Receptor as a Novel Regulator of Low-Density Lipoprotein Metabolism. Issue 2 (22nd January 2016) - Lu, Xifeng; Meima, Marcel E.; Nelson, Jessica K.; Sorrentino, Vincenzo; Loregger, Anke; Scheij, Saskia; Dekkers, Dick H.W.; Mulder, Monique T.; Demmers, Jeroen A.A.; M-Dallinga-Thie, Geesje; Zelcer, Noam; Danser, A.H. Jan
Abstract : Rationale: : The (pro)renin receptor ([P]RR) interacts with (pro)renin at concentrations that are >1000× higher than observed under (patho)physiological conditions. Recent studies have identified renin–angiotensin system–independent functions for (P)RR related to its association with the vacuolar H + -ATPase. Objective: : To uncover renin–angiotensin system–independent functions of the (P)RR. Methods and Results: : We used a proteomics-based approach to purify and identify (P)RR-interacting proteins. This resulted in identification of sortilin-1 (SORT1) as a high-confidence (P)RR-interacting protein, a finding which was confirmed by coimmunoprecipitation of endogenous (P)RR and SORT1. Functionally, silencing (P)RR expression in hepatocytes decreased SORT1 and low-density lipoprotein (LDL) receptor protein abundance and, as a consequence, resulted in severely attenuated cellular LDL uptake. In contrast to LDL, endocytosis of epidermal growth factor or transferrin remained unaffected by silencing of the (P)RR. Importantly, reduction of LDL receptor and SORT1 protein abundance occurred in the absence of changes in their corresponding transcript level. Consistent with a post-transcriptional event, degradation of the LDL receptor induced by (P)RR silencing could be reversed by lysosomotropic agents, such as bafilomycin A1. Conclusions: : Our study identifies a renin–angiotensin system–independent function for the (P)RR in the regulation of LDL metabolism by controlling the levels of SORT1 and LDL receptor. Abstract : Supplemental Digital Content is available in the text.